Negation and nonveridicality in the history of Greek - Chatzopulu, Katerina (Oxford studies in diachronic and historical linguistics, 2019)
This book provides a thorough investigation of the expression of sentential negation in the history of Greek, based on extensive data from major stages of the language. It also provides a new semantic interpretation of Jespersen's cycle that explains the Greek developments and those in other languages.